Искусительница: роман / Э. Ли ; пер. с англ. М. В. Келер - Ли Эйна (Шарм : коллекция, 2000)
Экземпляры: ф.19 (ретро) / Инвентарный номер: 38368 / Цена: / Сис.шифр: 84(4/8) / Авт.знак: Л 55 / ББК: 84(7Сое)